The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s00784-005-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors for temporomandibular disorders in a group of Mexican adolescents and youth adults

Abstract: The objective of the study was to determine the prevalence and associated factors for temporomandibular disorders (TMD) in a university sample of Campeche, Mexico. A cross-sectional study was carried out in 506 subjects aged 14-25 years. The subjects were requested to answer questionnaires concerning sociodemographic variables, history of stress, lifestyle, and anxiety. The Research Diagnostic Criteria for TMD (RDC/TMD) was used as TMD diagnostic system by four examiners capacitated and standardized. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
7
25

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(155 citation statements)
references
References 26 publications
5
118
7
25
Order By: Relevance
“…Anxiety in general has been reported to be a factor that is associated with sleep bruxism in adolescents and adults. 25,26 …”
Section: Sleep Bruxismmentioning
confidence: 99%
“…Anxiety in general has been reported to be a factor that is associated with sleep bruxism in adolescents and adults. 25,26 …”
Section: Sleep Bruxismmentioning
confidence: 99%
“…4,5 Among the factors involved in painful TMD pathogenesis, the role of sleep bruxism, awake bruxism, and parafunctional habits has been studied extensively in the adult population, 6 whereas there are few studies on this issue in the pediatric population. 7,8,9 In regard to sleep bruxism and awake bruxism, a recent international expert consensus suggested that there must be a clear differentiation between the two. 10 Sleep bruxism is classified as a sleep-related movement disorder, and defined as an oral activity characterized by grinding or clenching of the teeth during sleep, usually associated with sleep arousal.…”
Section: Introductionmentioning
confidence: 99%
“…Neste estudo, pelo menos um tipo de DTM foi observado em 35,5% dos participantes. Outros estudos que avaliaram a prevalência de DTMs em populações de adolescentes encontraram resultados com valores diferentes 2,4 . Entretanto, todos os autores evidenciam um dado em comum: a alta prevalência das DTMs, o que demonstra a necessidade de pesquisá-las em adolescentes.…”
Section: Discussionunclassified
“…As adolescentes têm 2,73 vezes mais chance de apresentar DTMs do que adolescentes do gênero masculino, achado concordante com resultados de outras investigações 2,4 . Essa incidência maior explica-se pelas diferenças estruturais presentes nas ATMs das mulheres 2 .…”
Section: Discussionunclassified
See 1 more Smart Citation